2018
DOI: 10.1007/s00223-018-0459-4
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the Transcription Factor PGC-1α in Mice Negatively Regulates Bone Mass

Abstract: Peroxisome proliferator-activated receptor-gamma coactivator (PGC1α) is a transcription coactivator that interacts with a broad range of transcription factors involved in several biological responses. Here, we show that PGC1α plays a role in skeletal homeostasis since aged PGC1α-deficient mice (PGC1α) display impaired bone structure. Micro-CT of the tibial mid-shaft showed a marked decrease of cortical thickness in PGC1α (- 11.9%, p < 0.05) mice compared to wild-type littermate. Trabecular bone was also impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…This result suggested that the elevated Receptor activator of nuclear factor kappa-Β ligand (RANKL) levels observed in bone marrow of knock-out mice could be the indirect mechanism through which osteoblasts increase osteoclast formation and activity in vivo. Moreover, in agreement with Lin and colleagues' study of 2004 [19], PGC1α knockout mice had 30% lower weight than control mice, lower ratio of inguinal white adipose tissue (iWAT)/body weight and strong decrease (~75%) in adipocyte area [12]. Colaianni and colleagues also evaluated, in iWAT, the uncoupling protein 1 (Ucp1) expression, considering its importance as a master gene involved in the trans-differentiation program from white adipocytes to adipocytes with a brown adipose tissue (BAT)-like phenotype [20].…”
Section: The Bone Phenotype Of Pgc1α Knock-out Micesupporting
confidence: 88%
See 3 more Smart Citations
“…This result suggested that the elevated Receptor activator of nuclear factor kappa-Β ligand (RANKL) levels observed in bone marrow of knock-out mice could be the indirect mechanism through which osteoblasts increase osteoclast formation and activity in vivo. Moreover, in agreement with Lin and colleagues' study of 2004 [19], PGC1α knockout mice had 30% lower weight than control mice, lower ratio of inguinal white adipose tissue (iWAT)/body weight and strong decrease (~75%) in adipocyte area [12]. Colaianni and colleagues also evaluated, in iWAT, the uncoupling protein 1 (Ucp1) expression, considering its importance as a master gene involved in the trans-differentiation program from white adipocytes to adipocytes with a brown adipose tissue (BAT)-like phenotype [20].…”
Section: The Bone Phenotype Of Pgc1α Knock-out Micesupporting
confidence: 88%
“…Increases Osteocalcin expression together with Nuclear related receptor-1 [8] Enhances Osteocalcin promoter activity interacting with Estrogen-related receptor alpha [9] Restores the inhibition of osteogenic differentiation and mitochondrial activity Sirtuin 3 knockdown-induced [10] Upregulates many key factors involved in osteoblast and osteocyte differentiation [11] PGC1α deletion causes a reduction in cortical thickness and in osteocalcin and collagen type I α 1 levels [12] PGC1α/β deficiency results in cortical and trabecular parameter reduction [11] PGC1α absence induces marrow adipose tissue accumulation [13] PGC1α activation in leptin receptor-deficient diabetic mice increases osteoblastic gene expression and inhibits atrogene transcription [14] In this review, we aim to summarize the current knowledge of the role of PGC1α as an anabolic factor in bone metabolism in both physiological condition and bone related pathologies, with the focus on paving the way for further studies in the future.…”
Section: In Vitromentioning
confidence: 99%
See 2 more Smart Citations
“…Structural parameters were ana-lyzed in reconstructed 3-dimensional images using evaluation software (μCT v1.6, Scanco Medical) according to the recommended guideline (18). The regions of interest were defined using previously described methods (37,38). The cancellous bone and marrow compartments of the L5 vertebral body were examined between the cranial and caudal growth plates.…”
Section: Methodsmentioning
confidence: 99%